Evening primrose, prickly pear and spiderwort flowers - Augustine, David, photographer (Colorado State University. Libraries, 2009)
White evening primrose, yellow prickly pear, lavender spiderwort flowers on the SGS, other plants.
Keywords: SGS; flowers; plants